Tarjīḥ Maqāṣidī Approach to Marriage Dispensation in Cases of Child Pregnancy in Indonesia - Aprilianto, Dwi; Isnaini, Enik; Shodiq, Ja’far; Dihya, Adindah Filzah Ukhtu; Marpuah, Siti (Al-Manahij: Jurnal Kajian Hukum Islam, 2026)
This study examines the legal and social paradox of marriage dispensation in Indonesia, particularly in cases of premarital pregnancy, where child protection objectives often conflict with the formal legitimacy of marriage. Although frequently justified as a protective legal mechanism, this article argues that marriage dispensation primarily functions as an emergency response, offering short-term legal relief while generating long-term social harm. Using a socio-legal and normative-empirical approach, the study applies the maqāṣid al-sharīʿah framework, particularly tarjīḥ maqāṣidī, to evaluate legal priorities in light of the higher objectives of Islamic law. Its novelty lies in measuring maṣlaḥah through multi-dimensional indicators scope, durability, precision, effectiveness, and temporal impact based on empirical data from Religious Courts and Women’s Empowerment and Child Protection agencies in East Java, Central Java, and West Java. The findings show that the benefits of marriage dispensation are limited to formal lineage recognition and stigma reduction. At the same time, its harms are extensive and enduring, including reproductive health risks, educational disruption, psychological vulnerability, and intergenerational poverty. From a maqāṣid perspective, this imbalance reflects a failure to protect life, intellect, and progeny. This study concludes that the marriage dispensation is normatively inconsistent and calls for prevention-oriented legal harmonization that prioritises child protection.